SEJARAH TRANSMIGRASI DAN KONDISI SOSIAL EKONOMI WARGA TRANSMIGRAN DI DESA SUKA DAMAI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU (Studi Perbandingan Sebelum dan Sesudah Transmigrasi) - Dian Husni Nurina; Drs. Ridwan Melay, M.Hum; Drs. Tugiman, MS ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Transmigration is a program of internal migration densely populated areas to sparsely populated areas. Transmigration in this era were successful in supporting the development of plantations and agricultural crops outside Java. One area of interest is the village of Suka Damai transmigration Tambusai Utara District of Rokan Hulu, Riau. Migrants in the village Suka Damai is a common resettlement program. The arrival of the first migrants to the village of pacifist is on 5 July 1982. The aim of this study was to determine (1) the history of transmigration village of Suka Damai Subdistrict Tambusai Utara. (2) the factors that influence the transmigration village of Suka Damai Subdistrict Tambusai Utara. (3) the mobility of intra-generation migrants village of Suka Damai Subdistrict Tambusai Utara. (4) mobility between generations homesteader village of Suka Damai Subdistrict Tambusai Utara. (5) the socio-economic conditions of migrants resident in the village of Suka Damai Subdistrict Tambusai Utara. (6) the relationship transmigration village Suka Damai Subdistrict Tambusai Utara with the area of origin. This study uses documents, interview and also using a questionnaire. Samples are 50 heads of families in the village of Suka Damai and informants in the study is the village in the early arrival of resettlement and transmigration community village of Suka Damai Subdistrict Tambusai Utara. The results showed that the transmigration village Suka Damai experienced success in socio-economic field. One of the things that drive the success of the community, namely migrants of their plantations and other ancillary businesses. This can be seen in the community migrants who have increased in the areas of income, their incomes initially 1,000-3,000 thousand every month in 1982 has now reached one million to 10 million every month. In the field of education migrants also increased, namely by following the educational program paket c. In the field of employment also increased, namely with the number of migrants moving from farm laborer to become farmers palm oil and rubber.Keywords: transmigration, social, economic.2